Dealing with shares on a shareholder's death: The plight of the deceased's personal representative - Halim, Akmal Hidayah; Mohd Salim, Wan Noraini; Hassan, Halyani; Mohd Noor, Nor Azlina; Arshad, Azhani (GATR Enterprise, 2015)
Objective – This paper aims to examine the extent of personal representative‘s duties and liabilities in dealing with shares on the death of a shareholder. The paper also analyses the procedure to administer the shares and the available options to the estate beneficiaries with regards to their entitlements to the shares.